25th ANNIVERSARY OF CLONING BY SOMATIC-CELL NUCLEAR TRANSFER: Cloning, mitochondrial replacement and genome editing: 25 years of ethical debate since Dolly. Issue 1 (11th June 2021) - Greenfield, Andy
Abstract : The birth of Dolly the sheep in 1996 elicited a tsunami of commentaries, both in the popular media and academic journals, including responses to the prospect of human reproductive cloning. Much of the anxiety expressed over this imagined consequence of Dolly's genesis revealed fundamental concerns about us losing our commitments to certain ethical goods, such as human dignity, or even 'what it means to be human'. Over the last 25 years, the focus of much of the ethical debate over human biotechnology has slowly shifted towards other genetic technologies that aim to influence inheritance, such as mitochondrial replacement techniques (MRT) and heritable genome editing. Genome editing, in particular, is a technology with multiple fields of application, actual and potential, in research and innovation. This review suggests that many of the fundamental concerns about the possibility of human reproductive cloning that were precipitated by Dolly persist today in the arguments of those who oppose MRT and any use of heritable human genome editing (HHGE). Whilst it is not accepted here that an understanding of human nature and dignity alone can demonstrate the ethical unacceptability of such assisted reproductive technologies, there are themes of justice, which extend into our relationships with animals, that demand continued wide-ranging examination and public dialogue. While Dolly has cast a long shadow over such discussions, this review suggests that the general existential angst over human uses of biotechnology that she came to symbolise is neither compulsory nor a reliable guide for how to think about biotechnologies today.